Legal Protection of Witness and Victim Protection Agency Against Reporting Witnesses (Case Study of Football League 3 Score Fixing Bribery) - Pamungkas, Sya’bana Putra (UMPurwokerto Law Review, 2022)
Abstract Whistleblowers often face terror threats that can threaten their lives or families when revealing crimes or violations they know. The role of the whistleblower is significant in disclosing a case, especially in soccer in Indonesia, one of which is the case of match-fixing. This study aims to determine the legal protection of whistleblower reporting witnesses in the match-fixing case in the Indonesian football league three and the barriers to the protection of the whistleblower reporting witness in the match-fixing case in the Indonesian league three football. The author’s method in this study uses a normative juridical method through a literature study that examines mainly secondary data in the form of legislation, court decisions, scientific journals, research results, and other references. The results show that Lasmi Indaryani as a whistleblower has received protection from the Witness and Victim Protection Agency (Lembaga Perlindungan Saksi Dan Korban, LPSK) through the mandate of Law No. 31 of 2014 concerning Witness and Victim Protection and strengthened by the Supreme Court Circular No. 4 of 2011 concerning Treatment For Whistleblowers (Whistle Blower). Obstacles often encountered in the implementation of duties and functions and the authority of LPSK in providing protection are barriers to legislation and cooperation between institutions, barriers to legislation, and cooperation between institutions. Keywords: Protection, whistleblower, match-fixing Abstrak Saksi pelapor (whistle blower) seringkali menghadapi ancaman teror yang dapat mengancam jiwanya atau keluarganya ketika mengungkap kejahatan atau pelanggaran yang diketahuinya. Peran whistle blower menjadi sangat penting dalam pengungkapan suatu kasus, terlebih dalam olahraga sepak bola di Indonesia salah satunya pada kasus pengaturan skor atau match fixing. Penelitian ini bertujuan untuk mengetahui perlindungan hukum terhadap saksi pelapor whistle blower dalam kasus pengaturan skor match fixing di sepakbola liga 3 Indonesia dan hambatan perlindungan Â saksi pelapor whistle blower dalam kasus pengaturan skor di sepakbola liga 3 Indonesia. Metode yang digunakan penulis dalam penelitian ini adalah menggunakan metode yuridis normatif melalui studi pustaka yang menelaah terutama data sekunder yang berupa peraturan perundang-undangan, putusan pengadilan, jurnal ilmiah, hasil penelitian dan referensi lainnya. Hasil penelitian menunjukkan bahwa Lasmi Indaryani sebagai whistle blower telah mendapatkan perlindungan oleh Lembaga Perlindungan Saksi Dan Korban (LPSK) melalui amanah Undang-Undang No.31 Tahun 2014 Tentang Perlindungam Saksi Dan Korban dan diperkuat oleh Surat Edaran Mahkamah Agung No.4 Tahun 2011 tentang Perlakuan Bagi Pelapor Tindak Pidana (Whistle Blower). Â Hambatan yang sering ditemui dalam pelaksanaan tugas dan fugsi, dan kewenangan LPSK dalam memberikan perlindungan adalah hambatan peraturan perundang-undangan dan kerjasama antar lembaga, hambatan peraturan perundang-undangan dan kerjasama antar lembaga. Kata Kunci: Perlindungan, whistleblower, match-fixing